Slurry Trench Method: A Case Study of Dalaman, Akköprü Dam, Turkey - Devrim ALKAYA; Burak YESIL (Engineering Research: Perspectives on Recent Advances Vol. 1, 2024)
In this study, slurry trench procedure implemented in Dalaman - Akköprü Dam, constructed by using rock embankments with a height of 163 m, was investigated as one of the biggest fill dams in Turkey. In the dam, impermeable curtains were constructed using the slurry trench method to control water infiltration from underground sources. This involved excavation and filling procedures in a cutoff trench approximately 50 meters deep. The construction methods and control criteria of these curtains constructed along the coffer dam axes under the upstream and downstream coffer dams were determined. As the result of the hydraulic pressure tests conducted on the alluvion, encountered as 43 m thick clay, sand, gravel, and block mix, the permeability coefficient values were found to be 10-3 - 10-4 cm/s. After the slurry trench method was applied, the permeability coefficient value was found as 10-7 cm/s and the desired permeability was achieved. The second important criterion is the strength value of concrete. The upper limit is determined as 2 MPa. Accordingly, in this study, 28-day compressive strength values were found between 710 - 760 kPa.